POSTMARKETING, PROSPECTIVE, MULTICENTRE, SINGLE-ARM STUDY OF SUBJECTS WHO RECEIVE AN INJECTION OF A MEDICAL DEVICE BASED ON HYALURONIC ACID: CLINICAL STUDY REPORT - Nazar Vadzyuk (World Science, 2024)
Introduction: Viscosupplementation with an intra-articular injection of hyaluronic acid (HA) is widely used around the globe for pain management in patients with osteoarthritis (OA). Safety and clinical outcomes are debated for decades. First, products have been designed for multiinjections (3–5 injections at 1-week intervals); newer products and treatment schemes are developing continuously. Elevated concentration or dose, additional components, and chemical bonds can provide better and prolonged effects of treatment. All these features could give an advantage like single-injection treatment, prolonged time between injections and better pain management. With the use of a single injection one can get advantages such as the reduction of visits to the doctor and less interventions with their associated risks. For this purpose, a benefit/risk profile of the novel HA formulation was investigated. This study contributes to knee osteoarthritis (KOA) treatment.Methods: Postmarketing, prospective, multicentre, single-arm study of subjects with knee OA grades II to IV according to the Kellgren and Lawrence classification was used who received a single injection of medical HA-based device was performed. The study has been scheduled in the form of Visit 1 (month 0), Visit 2 (month 1), Visit 3 (month 2), Visit 4 (month 3), Visit 5 (month 4), Visit 6 (month 5) and Visit 7 (month 6). The changes in the WOMAC questionnaire have been evaluated upon treatment initiation for up to 6 months. The incidences of adverse events have been recorded throughout the study.Results: The clinical study was conducted in Ukraine and Poland by 5 clinical sites; 55 persons who met the study inclusion criteria were involved in the investigation. The age of subjects ranged from 36 to 80 years with mean age of 52.02 years. The score of the WOMAC questionnaire findings resulted in the improvement of pain and function after 1, 2, 3, 4, 5, 6 months compared to the population's baseline data (mean reduction from baseline 13.62, 18.31, 22.79, 22.18, 21.25, 21.55 points, respectively (p<0.001)).Conclusion: This study showed HA's tolerability and safety in a single-injection application for at least 24 weeks, resulting in a promising treatment option for patients with KOA for whom conventional therapy has failed.